Time Required for Education Up to College Level - Kusuma, Kumara Adji (Indonesian Journal of Public Policy Review, 2024)
This study explores the imperative of mandatory college education in Indonesia, amidst recent protests against rising tuition fees. Despite higher education's recognized socio-economic benefits, Indonesia has yet to mandate college attendance, lagging behind global trends. Drawing on comparative analysis with Malaysia, South Korea, and European nations, the research underscores the potential of mandatory college education to enhance workforce skills, promote innovation, and reduce social disparities. Findings advocate for government commitment, increased funding, and collaboration with the private sector to ensure equitable access and quality in higher education, ultimately driving economic growth and social development. Highlights : Global Trends Comparison: Benchmarks Indonesia against leading nations for educational policy insight. Equitable Access and Quality: Ensuring fairness and standards for a skilled, diverse workforce. Government-Private Sector Collaboration: Partnerships vital for sustainable funding and educational enhancement. Keywords: Mandatory Education, Indonesia, Socio-Economic Benefits, Collaboration, Funding